Hup Lee Coffee Trading Management System - Phua, Huaysze; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2025)
The Hup Lee Coffee Trading Management System, currently reliant on manual processes, encounters challenges in document control, inventory management, and decision-making inefficiencies. The study proposes developing a web-based coffee trading management system to address these issues, emphasizing efficient order processing, customer management, and reporting. This project aims to enhance inventory management, minimize errors, and optimize operational processes. Conducted at Hup Lee Coffee Trading’s primary facility in Selangor, Malaysia, the study involves interactions with key personnel to implement and test the system’s modules. The expected outcomes include improved inventory control, real-time reporting for informed decisions, enhanced productivity through efficient document retrieval, and streamlined data search capabilities.